The RISK MANAGEMENT IN FIREFIGHTING FOR BUILDINGS WITH PHOTOVOLTAIC SYSTEMS. (Social and Environmental Law Journal, 2023)
As the use of solar energy in buildingsincreases, the operations developed by the Military Fire Departments have become more dangerous and expose operators to unknown risks. Therefore,to stablish proper and standardized procedures that guarantee firefighters safety,it is necessary to be familiar with the photovoltaic generation systems, identify and analyze the risks involved in operating systems and installations. Another important aspect is to verify the existence of devices that can be inserted into the systems to avoid accidents during calls. In this approach, the purpose of this article is to present, through the Preliminary Risk Analysis - APR technique, the management of potential risks that expose firefighters in structural firefighting operations in buildings that make use of photovoltaic systems, for the generation of electric energy, to prevent, mitigate and control the dangers intrinsic to these events.Methodologically, it was classified as applied research as well asbased on deductive method, descriptive, qualitative, bibliographic and documental. It was possible to outline important aspects that a Standardized Operational Procedure should attain to.